Role of stimulating growth factor 2 and galectin-3 in predicting the ventricular tachyarrhythmias in patients with ischemic cardiomyopathy - T. A. Atabekov; R. E. Batalov; S. I. Sazonova; A. M. Gusakova; S. N. Krivolapov; M. S. Khlynin; S. V. Popov (Кардиоваскулярная терапия и профилактика)
Aim. To assess the role of stimulating growth factor 2 (ST-2) and galectin-3 in predicting the ventricular tachyarrhythmias (VTA) in patients with coronary artery disease (CAD) and left ventricular ejection fraction (LVEF) <35%.Material and methods. The study included 40 patients (men, 36 (90,0%); median age, 64,5 [57,5; 68,5] years) with CAD, NYHA class IIIII heart failure, LVEF <35%, indications for implantable cardioverter defibrillator (ICD) (primary prevention of sudden cardiac death). Prior to ICD implantation, patients were measured for serum ST-2 and galectin-3 levels. For 18 months, patients were assessed for arrhythmic events recorded in the ICD memory.Results. The 1st group consisted of 10 (25,0%) patients who had VTA episodes, arrested by antitachycardia pacing or shock during 18-month follow-up. The 2nd group consisted of 30 (75,0%) patients without VTA episodes. It was found that ST-2 concentration >22,48 ng/ml (p=0,02) and galectin-3 >10,95 ng/ml (p=0,009) corresponded to appropriate ICD discharge. Multivariate ROC analysis demonstrated that the only independent predictor of VTA was ST-2 elevation (odds ratio, 1,11; 95% CI, 1,01-1,21; p=0,023).Conclusion. An increase in the concentration of both ST-2 >22,48 ng/ml and galectin-3 >10,95 ng/ml had a high predictive value in assessing the VTA risk in patients with ischemic cardiomyopathy. In multivariate analysis, an increase in ST-2 >22,48 ng/ml was an independent predictor of VTA.